Parental well-being in times of Covid-19 in Germany - Mathias Huebener; Sevrin Waights; Christa Katharina Spieß; Nico A. Siegel; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We examine the differential effects of Covid-19 and related restrictions on individuals with dependent children in Germany. We specifically focus on the role of school and day care center closures, which may be regarded as a "disruptive exogenous shock" to family life. We make use of a novel representative survey of parental well-being collected in May and June 2020 in Germany, when schools and day care centers were closed but while other measures had been relaxed and new infections were low. In our descriptive analysis, we compare well-being during this period with a pre-crisis period for different groups. In a difference-in-differences design, we compare the change for individuals with children to the change for individuals without children, accounting for unrelated trends as well as potential survey mode and context effects. We find that the crisis lowered the relative well-being of individuals with children, especially for individuals with young children, for women, and for persons with lower secondary schooling qualifications. Our results suggest that public policy measures taken to contain Covid-19 can have large effects on family well-being, with implications for child development and parental labor market outcomes.
Keywords: D1; H12; H75; I2; 330; well-being; Covid-19; Corona virus; day care closures; school closures; COMPASS; SOEP